TAPT1 interacts with SUCO to maintain the homeostasis of newly synthesized proteins and brain development in mice - Jiawei Gao; Fuqiang Yang; Yisheng Jiang; Yu Zheng; Lu Cai; Xiahe Huang; Li Yuan; Yingchun Wang; Yaqing Wang; Zhiheng Xu (Proceedings of the National Academy of Sciences, 2025)
Genetic mutations in Tapt1 cause complex skeletal dysplasia and structural brain abnormalities. Although the pathogenesis underlying skeletal dysplasia has been explored, the functions and potential mechanisms of transmembrane anterior–posterior transition 1 (TAPT1) during brain development have not been reported. Here, we show that the brains of Tapt1 conditional knockout mice exhibit severe neurodevelopmental defects, including impaired proliferation and differentiation of neural progenitor cells and defects in dendritic and synaptic development, leading to severe microcephaly, motor dysfunction, and early death. Mechanically, we reveal that TAPT1 interacts with SUCO in the endoplasmic reticulum to maintain newly synthesized proteins, including those important for brain development. The TAPT1–SUCO complex plays an essential role in the homeostasis of newly synthesized proteins, and its loss causes overactivated protein degradation, as well as impaired endoplasmic reticulum-to-Golgi trafficking and organelle structures. Our results thus provide insights into the pathogenesis of TAPT1 and SUCO mutation–associated diseases that share similar pathologies.